GENETIC STRUCTURE OF THE RED VOLE MYODES (= CLETHRIONOMYS) RUTILUS PALLAS, 1779 POPULATIONS OF THE NORTHERN PRIOKHOTYE WITH REGARD TO NUCLEOTIDE SEQUENCE VARIABILITY OF THE MTDNA CYTb GENE - V. V. Pereverzeva; A. A. Primak; E. A. Dubinin (Вавиловский журнал генетики и селекции)
The purpose of the work was to determine the genetic structure of coastal populations of the species Myodes (=Clethrionomys) rutilus in the Northern Priokhotye on the base of the variability of a partial mt DNA cytb sequence. For the first time, the nucleotide and haplotypic variability of cytb gene, as well as the genetic structure of the red vole populations in Matykil, Nedorazumeniya, Spafar’eva and Talan islands (Northern Priokhotye ); Koni peninsula; the outskirts of Magadan; and the Yama river region were determined. The insular red vole populations have unique gene pools comprising two to three haplotypes. A high level of cytb gene polymorphism was found in M. rutilus from the continental coast of the Sea of Okhotsk. The existence of a contiguous coastal red vole population in the Northern Priokhotye is suggested. Genetic data evidence that М. rutilus from the islands of Tauysk Bay and the continental coast of the Sea of Okhotsk belong to the same maternal lineage, whereas the red vole from Matykil island pertains to another genetic branch.